Dewey, Technological Thinking and the Social Studies: The Intelligent use of Digital Tools and Artifacts - Stuckart, Daniel W.; Rogers, James D. (European Scientific Journal, ESJ, 2017)
Since the emergence of computer technologies in education in the 1970s, social studies teacher educators have advocated for the effective use of digital tools and artifacts (DTAs) in student learning. After nearly four decades, researchers still report low-level cognitive uses and overwhelmingly traditional teaching methods. Perhaps one reason for the lack of progress is the absence of clear guidelines and theoretical constructs. The purpose of this manuscript is to place the use of DTAs within the context of John Dewey’s philosophy, and along the way, articulate guidelines for integrating technology in the social studies. By constructing a philosophical framework based on Deweyan thought, one can test research and ideas, perhaps leading to the more purposeful and effective use of these tools and artifacts in teaching and learning. Philosophy is an instrument for criticizing and reconstructing human activities, and scholars belatedly credit Dewey as a pioneer in the technology branch.